Christmas survival [videorecording (DVD)] - Dearden, James, 1949-; Ovenden, Julian; Whelan, Gemma, 1981-; Richardson, Joely; Landes, Michael, 1972- (Gravitas Ventures, 2019)
Two sisters come together to spend Christmas with their families in their recently deceased parents' falling down English country house, with hilariously chaotic consequences, as ancient sibling rivalries flare up again to sabotage the hoped-for season of good will.